2008
DOI: 10.1093/scan/nsn009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating face trustworthiness: a model based approach

Abstract: Judgments of trustworthiness from faces determine basic approach/avoidance responses and approximate the valence evaluation of faces that runs across multiple person judgments. Here, based on trustworthiness judgments and using a computer model for face representation, we built a model for representing face trustworthiness (study 1). Using this model, we generated novel faces with an increased range of trustworthiness and used these faces as stimuli in a functional Magnetic Resonance Imaging study (study 2). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
317
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(345 citation statements)
references
References 36 publications
23
317
2
3
Order By: Relevance
“…One way that trust can signal religiosity is through a person's facial features. In fact, previous research has found that people tend to think that others with pronounced cheekbones, raised inner eyebrows, wide chins, and shallow nose sellions are trustworthy (Todorov, Baron, & Oosterhof, 2008). We predict that mental images of theists would have gestalt facial physiognomies that display positive attributes, especially in the domains of morality and trustworthiness.…”
Section: Perceiving Religiosity In a Facementioning
confidence: 79%
“…One way that trust can signal religiosity is through a person's facial features. In fact, previous research has found that people tend to think that others with pronounced cheekbones, raised inner eyebrows, wide chins, and shallow nose sellions are trustworthy (Todorov, Baron, & Oosterhof, 2008). We predict that mental images of theists would have gestalt facial physiognomies that display positive attributes, especially in the domains of morality and trustworthiness.…”
Section: Perceiving Religiosity In a Facementioning
confidence: 79%
“…Furthermore, the current research extends earlier research in social psychology (Jeanquart-Barone and Sekaran, 1994;Todorov and Oosterhof, 2011) showing that facial characteristics of a distinctly non-human, robotic social entity can activate trustworthiness judgments and trusting behavior. Earlier research (Todorov et al, 2008(Todorov et al, , 2015 showed that facial characteristics of artificial faces on the screen could influence trustworthiness judgments of human perceivers. Importantly, the current results are the first to show these effects in the context of human-robot interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It also examines whether facial characteristics engender trust in line with how Todorov et al (2008) found that people judge trustworthiness from photos. Besides, this study also investigates how trust toward a robotic persuader can influence psychological reactance.…”
Section: Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…During social interactions, we make rapid judgments about new people that determine whether to approach or avoid and shape our future interactions with them (21). Individuals paired with positive valence characteristics are rated as more likeable and approachable but the opposite for those with negative information (22).…”
mentioning
confidence: 99%